2008
DOI: 10.3102/0002831207312906
|View full text |Cite
|
Sign up to set email alerts
|

Back to the Future: Directions for Research in Teaching and Teacher Education

Abstract: In this article, the authors examine two distinct but closely related fields, research on teaching and research on teacher education. Despite its roots in research on teaching, research in teacher education has developed in isolation both from mainstream research on teaching and from research on higher education and professional education. A stronger connection to research on teaching could inform the content of teacher education, while a stronger relationship to research on organizations and policy implementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
541
0
45

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 850 publications
(602 citation statements)
references
References 38 publications
(50 reference statements)
16
541
0
45
Order By: Relevance
“…The findings of this study illustrated the value of closely linking theory to practice, and confirmed that close collaboration between University tutors, mentors and PSTs enhanced the learning and development process (Grossman and McDonald, 2008;Shulman and Shulman, 2004).…”
Section: Some Of Them Are Willing To Take Great Risks Thomas With Thsupporting
confidence: 51%
See 1 more Smart Citation
“…The findings of this study illustrated the value of closely linking theory to practice, and confirmed that close collaboration between University tutors, mentors and PSTs enhanced the learning and development process (Grossman and McDonald, 2008;Shulman and Shulman, 2004).…”
Section: Some Of Them Are Willing To Take Great Risks Thomas With Thsupporting
confidence: 51%
“…The importance of situated learning experiences, as well as the wider social and cultural setting in which these occur is highly significant (Grossman and McDonald, 2008;Korthagen, 2010;Shulman and Shulman, 2004), influencing learning through enculturation, professional socialisation and co-construction (Curtner-Smith, Hastie and Kinchin, 2008;Green, 2006;Keay, 2005;Miller, 2009;Sirna, Tinning and Rossi, 2010). Shulman and Shulman's (2004) use of the term CoP has been employed to clarify the position and use of CoP taken in this paper.…”
Section: A Theoretical Framework In Teacher Knowledge Researchmentioning
confidence: 99%
“…Participants in Fernandez"s and Robinson"s (2007) study pointed out that "microteaching lesson study" (MLS) provided them with opportunities to bridge the gap between theory and practice and to develop reflective learning strategies. In the present study, a number of students (16) stated that microteaching provided them with practical experiences to learn effective classroom management procedures, lesson planning and time management. These students stated, "we learned about classroom management.…”
Section: Microteaching Often Allows Us To Use Information and Theoriementioning
confidence: 84%
“…Grossman and McDonald (2008) indicated that such opportunities allow student teachers to experiment with aspects of practice and then learn from that experience. Microteaching application is considered a suitable approach to meet the above-mentioned recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…The need to refer to the effect of contextual factors within teacher education is a highlighted aspect in research on teacher education undertaken by Grossman and McDonald (2008). School climate including such elements as parent/community relations, administration, studentís behavioral values was found to be related to emotional exhaustion, depersonalization, and feelings of low personal accomplishment, which cause burnout for all together.…”
Section: Contextual Factors In Teacher Educationmentioning
confidence: 99%